2022
DOI: 10.1021/acs.organomet.2c00127
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Behavior of Acylthiourea Ligands in Their Ru(II)–Benzene Complexes─Structures and Anticancer Activity

Abstract: Acylthiourea ligands have applications in both synthetic and applied chemistry. The skeleton of the ligand contains several heteroatoms which offer variable coordination modes in their complexes. Herein, we report one such erratic behavior of these types of complexes upon crystallization. Six Ru­(II)–benzene complexes (B1–B6) containing the acylthiourea ligand were synthesized and adequately characterized using analytical and spectroscopic techniques. In contrast to the spectroscopic data confirming the monode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In contrast to the results obtained from spectroscopy, an unusual bidentate coordination of the furoylthiourea ligands through N, S atoms with the Ru­(II) ion was seen in complexes 1 and 3 , whereas the monodentate coordination involving only S was observed in complexes 4 and 6 . Such N, S coordination of aroylthiourea ligands with Ru­(II)-arene in the solid state has already been reported by Cunha, Parveen, Obradović, and Swaminathan et al , Figure illustrates the thermal ellipsoid plots for the ligands and complexes, as well as the atomic labeling schemes. Crystal data and selected bond lengths and angles for the ligands and complexes are summarized in Tables S2–S5.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…In contrast to the results obtained from spectroscopy, an unusual bidentate coordination of the furoylthiourea ligands through N, S atoms with the Ru­(II) ion was seen in complexes 1 and 3 , whereas the monodentate coordination involving only S was observed in complexes 4 and 6 . Such N, S coordination of aroylthiourea ligands with Ru­(II)-arene in the solid state has already been reported by Cunha, Parveen, Obradović, and Swaminathan et al , Figure illustrates the thermal ellipsoid plots for the ligands and complexes, as well as the atomic labeling schemes. Crystal data and selected bond lengths and angles for the ligands and complexes are summarized in Tables S2–S5.…”
Section: Resultssupporting
confidence: 76%
“…On the contrary, photomicrographs of the organs treated with cisplatin showed severe inflammation and edema of the kidneys, degeneration of the distal and proximal epithelial cells, accumulation of vesicles in the cytoplasm, and damage to the alveolar sacs. From these histological images, it is evident that the administration of Ru­(II) complexes 6 and 12 in the mice models did not cause any obvious damage to the organ tissues …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…To ensure the purity of the final product, the isolated precipitate was subjected to multiple washes with hexane. Finally, the purified precipitate was dried under vacuum conditions …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The proliferation of MSNP@poly(HEMA-co-PEGMA-g-DOX/R6G) and DOX to SNU-668 cells was evaluated by the MTT analysis [49][50][51]. The cytotoxicity curves showed that both MSNP@poly(HEMA-co-PEGMA-g-DOX/R6G) and DOX alone had substantial negative impacts on the proliferation and growth of SNU-668 cells (figure 7).…”
Section: Cytotoxicity and Fluorescence Findingsmentioning
confidence: 99%